2020
DOI: 10.1038/s41598-020-61811-8
|View full text |Cite
|
Sign up to set email alerts
|

Controllable movement of single-photon source in multifunctional magneto-photonic structures

Abstract: open Scientific RepoRtS | (2020) 10:4843 | https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our results point out that miniaturization amplifies such effects, enabling photochemical reactions which would be regarded as inactive at mild (visible) spectral regions at larger scales. While low absorption has been previously used to enable subdiffractive fabrication processes, [41][42][43] we now suggest that several other photochemical processes could be similarly concerned, highlighting the importance of quantitative and sensitive measurements for understanding local surface modification at the micro and nanoscales.…”
Section: Wavelength Dependencymentioning
confidence: 86%
“…Our results point out that miniaturization amplifies such effects, enabling photochemical reactions which would be regarded as inactive at mild (visible) spectral regions at larger scales. While low absorption has been previously used to enable subdiffractive fabrication processes, [41][42][43] we now suggest that several other photochemical processes could be similarly concerned, highlighting the importance of quantitative and sensitive measurements for understanding local surface modification at the micro and nanoscales.…”
Section: Wavelength Dependencymentioning
confidence: 86%
“…The authors demonstrated the external control of the structures in three dimensions using magnetic fields. The same group extended their efforts in a following work showing the capabilities of SU-8 based NCPRs for the fabrication of 2D and 3D magneto-photonic devices through LOPA DLW (Au et al, 2020). Lastly, Augurio et al proposed a multifunctional nanocomposite hydrogel which could be used for tracking (optical) and manipulation (magnetic) (Augurio et al, 2020).…”
Section: Luminescent Nanofillersmentioning
confidence: 95%
“…In particular, UCNPs based on the energy transfer mechanism between sensitized and activator dopants have been extensively developed in recent years due to the capabilities of the chemical synthesis, their chemical endurance, low toxicity and excellent optical stability (Wang et al, 2010;Chen et al, 2014). Luminescent NCPRs have many applications: photo-curing of PRs with embedded QDs has been studied for on-chip detection of heavy metal ions (Xu et al, 2013), bar-coding particles (Zhao et al, 2011), development of high quality displays (Li et al, 2019c) and deterministic integration of quantum emitters into waveguides (Lio et al, 2019;Xu et al, 2020b), nanoantennas (Broussier et al, 2019) and remotely controllable magnetic structures (Au et al, 2020). A recent review by Smith et al contains a section on lithographically pattered QD NCPRs (Smith et al, 2019).…”
Section: Luminescent Nanofillersmentioning
confidence: 99%
“…Using magnetic fields, the structure can be manipulated. Adapted with permission from Au et al 98 Copyright 2010 by original authors (CC BY). 98 This journal is © The Royal Society of Chemistry 2024 deterministically coupled to CdSe/CdS CQDs embedded in a dielectric slab (Fig.…”
Section: Positioning Of Individual Emittersmentioning
confidence: 99%